2016
DOI: 10.1186/s12903-016-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-level laser therapy in accelerating tooth movement, preventing relapse and managing acute pain during orthodontic treatment in humans: a systematic review

Abstract: BackgroundRecently low-level laser therapy (LLLT) has been proposed to improve orthodontic treatment. The aims of this systematic review were to investigate the scientific evidence to support applications of LLLT: (a) to accelerate tooth movement, (b) to prevent orthodontic relapse and (c) to modulate acute pain, during treatment with fixed appliances in children and young adults.MethodsTo ensure a systematic literature approach, this systematic review was conducted to Goodman’s four step model. Three database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 32 publications
1
24
0
6
Order By: Relevance
“…The studies that have found that laser therapy decreases [25][26][27][28][29][30][31] or does not decrease [19,24,32] pain are difficult to directly compare with the present results. Among the four studies that used a VAS and true placebo controls, two detected significant laser effects on pain agreeing with our results [28,29], while the remaining reported no treatment effect [19,24,32,33]. The differences among the studies are probably due to the different power, energy, and wavelength settings used (Table 3) [19,29].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The studies that have found that laser therapy decreases [25][26][27][28][29][30][31] or does not decrease [19,24,32] pain are difficult to directly compare with the present results. Among the four studies that used a VAS and true placebo controls, two detected significant laser effects on pain agreeing with our results [28,29], while the remaining reported no treatment effect [19,24,32,33]. The differences among the studies are probably due to the different power, energy, and wavelength settings used (Table 3) [19,29].…”
Section: Discussionsupporting
confidence: 85%
“…The literature clearly shows a difference of laser parameters in the treatments for pain and orthodontic movement [10,11,13,29,[33][34][35]. In the treatment of pain, both potency and higher doses have presented better results.…”
Section: Discussionmentioning
confidence: 99%
“…Full texts of the 26 studies were retrieved and were evaluated according to the inclusion and exclusion criteria. Finally, 11 SRs were included in our review . The detailed literature search process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Doshi-Mehta e Bhad-Patil (2012), Youssef et al (2008) e Qamruddin et al (2017) consideraram eficaz o laser para reduzir os níveis de dor; entretanto, Limpanichkul et al (2006) não encontraram nenhuma diferença significante. Os efeitos colaterais do tratamento com LBI devem ser considerados antes do seu uso na prática clínica (SONESSON et al, 2016). O movimento acelerado aumenta o risco de reabsorção radicular; mas, apenas dois estudos utilizaram radiografias para monitorar essas possíveis alterações radiográficas (DOSHI-MEHTA e BHAD-PATIL, 2012;SOUSA et al, 2011).…”
Section: Discussionunclassified